The impact of Wilson disease on myocardial tissue and function: a cardiovascular magnetic resonance study - Salatzki, Janek; Mohr, Isabelle; Heins, Jannick; Çerçi, Hüseyin Mert; Ochs, Andreas; Paul, Oliver; Riffel, Johannes; André, Florian; Hirschberg, Kristóf; Müller-Hennessen, Matthias; Giannitsis, Evangelos; Friedrich, Matthias; et al. (Journal of cardiovascular magnetic resonance, 2021)
Systemic effects of altered serum copper processing in Wilson Disease (WD) might induce myocardial copper deposition and consequently myocardial dysfunction and structural remodeling. This study sought to investigate the prevalence, manifestation and predictors of myocardial tissue abnormalities in WD patients.
Gesehen am 30.06.2022